Switching on Power Harmonic Filters - Yuriy Varetsky (Energy Engineering and Control Systems)
In modern industrial power supply systems, there is observed rapid growth of time varying nonlinear loads having low power factor. The most adequate engineering solution for reactive power compensation of the loads is using compensation units including multiple single tuned passive filters. The practice of operating multiple single tuned filter circuits in the power supply systems has shown that switching transients in the supply system can generate high overvoltages and overcurrents on the filter circuit components. Rated parameters of the filter capacitor and reactor are characterized by the certain manufacturing tolerances. So, filter tuning depends on the tolerances. The impact of the filter tuning on switching transient behaviour under harmonic filters energizing has been analysed in the study.